This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: ECEN 646 Homework 6 Solutions 1 C ¸inlar Exercise (8.4), Chapter 4 We are interested in every 13 th arrival in a Poisson process. (a) The interarrival times in a Poisson process are exponentially dis tributed. The lucky arrivals are separated by 12 unlucky ones and so the time between 2 lucky arrivals is the sum of 13 exponential random variables i.e. an Erlang(13) random variable. f T ( t ) = λe λt ( λt ) 12 12! t ≥ (b) Let N t be the number of arrivals in the interval [0 ,t ]. The number of gifts M t given would then be equal to the number of integer multiples of 13 contained in N t . The event { M t = k } is the same as the event { 13 k ≤ N t ≤ 13 k + 12 } P ( M t = k ) = P (13 k ≤ N t ≤ 13 k + 12) = 12 summationdisplay i =0 P ( N t = 13 k + i ) = 12 summationdisplay i =0 e λt ( λt ) 13 k + i (13 k + i )! No further simplification is possible. 2 C ¸inlar Exercise (8.10), Chapter 4 We have a family of Poisson processes out of which we choose one based on the outcome of a random experiment. The outcome of the random ex periment takes value i with probability π ( i ). (a) Conditioned on the event { X = i } , the process N is a Poisson process with rate λ ( i ). So, the unconditional distribution of N t can be found by conditioning on the value of X . 1 P { N t = k } = summationdisplay i ∈ E P ( N t = k  X = i ) P ( X = i ) = summationdisplay i ∈ E π ( i ) e λ ( i ) t ( λ ( i ) t ) k k ! k = 0 , 1 ,... (b) For a process to have independent increments, the events { N t + s − N t } and { N t } should be independent. In this case, it suffices to show that P ( N t + s − N t = k 1  N t = k 2 ) negationslash = P ( N t + s − N t = k 1 ) P ( N t + s − N t = k 1  N t = k 2 ) = P ( N t + s − N t = k 1 and N t = k 2 ) P ( N t = k 2 ) Since the process in question is no longer a simple Poisson process, we can’t assume that the two events in the numerator are independent. However, conditioned on the the event { X = i } , the process is Poisson. Hence, we can use the law of total probability to evaluate the numerator just as we did in part ( a ). P ( N t + s − N t = k 1 and N t = k 2 ) = summationdisplay i ∈ E P ( N t + s − N t = k 1 and N t = k 2  X = i ) P ( X = i ) = summationdisplay i ∈ E π ( i ) P ( N t + s ( i ) − N t ( i ) = k 1 ) P ( N t ( i ) = k 2 ) = summationdisplay i ∈ E π ( i ) e λ ( i )...
View
Full
Document
This note was uploaded on 01/19/2012 for the course ECEN 646 taught by Professor Serapsavari during the Fall '11 term at Texas A&M.
 Fall '11
 SerapSavari

Click to edit the document details